2019
DOI: 10.1080/19475705.2018.1536080
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distributions of landslides in the Qinba Mountains, Shaanxi Province, China

Abstract: The spatial and temporal distributions of landslides can be used to assess the potential future impacts of landslides over large scales. However, quantitatively characterizing the spatial and temporal distributions of landslides and their causes remains a critical challenge. In this work, a typical landslide-prone region (the Qinba Mountains) is selected to identify this spatial and temporal trend. Information on 295 landslides spanning ten years from 2005 to 2014 was collected. The results revealed that lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 76 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…Qiu et al () studied 295 historical landslides (2005–2014) in a 74,000‐km 2 region of the Qinba Mountains, China. Qiu et al () found the cumulative frequency distribution of the number of landslides occurring per day followed a power function distribution with a scaling exponent of −1.18 (with number of landslides per day ranging from 1 to 100). Most days in the time series had zero landslides; this value was not included in the scaling analysis.…”
Section: Scaling Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Qiu et al () studied 295 historical landslides (2005–2014) in a 74,000‐km 2 region of the Qinba Mountains, China. Qiu et al () found the cumulative frequency distribution of the number of landslides occurring per day followed a power function distribution with a scaling exponent of −1.18 (with number of landslides per day ranging from 1 to 100). Most days in the time series had zero landslides; this value was not included in the scaling analysis.…”
Section: Scaling Propertiesmentioning
confidence: 99%
“…Spatial patterns of landslide locations have been found to exhibit power scaling properties (Goltz, 1996;Guthrie & Evans, 2004b;Liucci et al, 2015;Qiu et al, 2019). Guthrie and Evans (2004b) and Qiu et al (2019), using nearest neighbor analysis and density contour methods, found that the spatial distribution of landslides cluster and that intraday rainfall magnitudes and earthquake occurrences correlate with the clustering of landslides within the study areas.…”
Section: Spatial Scaling and Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Landslide hazard may be defined as the probability of a damaging landslide in a spatial ("where") and temporal ("when") context, along with the magnitude ("how large") of the event [6,7]. Landslide susceptibility is defined as the likelihood of landslide occurrence ("where") in an area depending on local terrain conditions [8].…”
Section: Introductionmentioning
confidence: 99%